(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Fibroblast growth factor 2 (FGF2) is a potent mitogenic factor of cortical fibroblasts and induces kidney fibrosis. We hypothesized that serum levels of FGF2 has an association with the severity of vesicoureteral reflux (VUR) and renal parenchymal scar. Materials and Methods. Between 2007 and 2009, a total of 28 children with VUR were enrolled in this study and were compared with 52 healthy children. All children with VUR underwent technetium Tc 99m dimercaptosuccinic acid renal scintigraphy. Fibroblast growth factor 2 was measured in both groups. Results. The mean level of FGF2 was 65.0 ± 19.0 pg/mL in the VUR group and 62.5 ± 15.3 pg/mL in the control group (P > .05). There was no correlation between serum levels of FGF2 and sex, age, or the grade of VUR. Of the 28 children with VUR, 19 had renal parenchymal scar on dimercaptosuccinic acid renal scintigraphy. The mean serum level of FGF2 was not significantly different in the children with and without renal parenchymal scar. Conclusions. This study showed no correlation between serum FGF2 and renal parenchymal scar or grade of VUR.